Exploring the 21st Century Skills and Science Teaching Pedagogy: Profiles, Readiness, and Barriers - Tomo Djudin (STKIP Singkawang, 2020)
The main objective of this study is to explore the extent of teachers’ readiness in anticipating the demands of 21st century skills and science teaching pedagogy practice. A quantitative survey-descriptive method employed in this study. The sample consists of 120 public primary school teachers in Pontianak. A five responses Likert scale questionnaire comprises 37 items was administered. Data were analysed by using descriptive statistical analysis, the independent t-test, and the extent of readiness was interpreted according to the interval of the overall average score. Based on data analysis, it is found that the total profile of “never and seldom” teachers’ responses is 9.2%, the “often and always” is 20.0%, and “sometimes” is 70.8%. There is no total means score difference between experienced and novice teachers’ performance (t = 0.887, p > 0.05). Moreover, the barrier factors the teachers faced in schools could be categorized as professional development, personal, institutional, and technological factor. This study concluded that the readiness of public primary school teachers in Pontianak in implementing the 21st century skills and science teaching pedagogy is an insufficient category. In-service teacher training for ICT integration should be directed toward building teachers’ skills and competencies in science pedagogical practices.